The biological mechanisms regulating sperm selection by the ovine cervix. Issue 1 (July 2019) - Fair, S; Meade, K G; Reynaud, K; Druart, X; de Graaf, S P
Abstract : In species where semen is deposited in the vagina, the cervix has the unique function of facilitating progress of spermatozoa towards the site of fertilisation while also preventing the ascending influx of pathogens from the vagina. For the majority of species, advances in assisted reproduction techniques facilitate the bypassing of the cervix and therefore its effect on the transit of processed spermatozoa has been largely overlooked. The exception is in sheep, as it is currently not possible to traverse the ovine cervix with an inseminating catheter due to its complex anatomy, and semen must be deposited at the external cervical os. This results in unacceptably low pregnancy rates when frozen-thawed or liquid stored (>24 h) semen is inseminated. The objective of this review is to discuss the biological mechanisms which regulate cervical sperm selection. We assess the effects of endogenous and exogenous hormones on cervical mucus composition and discuss how increased mucus production and flow during oestrus stimulates sperm rheotaxis along the crypts and folds of the cervix. Emerging results shedding light on the sperm-cervical mucus interaction as well as the dialogue between spermatozoa and the innate immune system are outlined. Finally, ewe breed differences in cervical function and the impact of semen processing on the success of fertilisation, as well as the most fruitful avenues of further investigation in this area are proposed.